2017
DOI: 10.1155/2017/7873951
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Barriers towards Provision of Health Promotion Services among Community Pharmacists in Gondar, Northwest Ethiopia

Abstract: Background Health promotion is now becoming an integral part of community pharmacy practice worldwide. Objectives This study was intended to determine the level of involvement of community pharmacists in providing health promotion service and to identify the barriers to the practice. Methods A cross-sectional study was conducted on 48 community pharmacists working in Gondar town, Northwest Ethiopia. Data on sociodemographic factors, practice, and barriers to health promotion service were collected and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
1
20
2
Order By: Relevance
“…These findings are consistent with the result from a previous study which reported that female pharmacists were significantly more involved than males in providing general health promotion services and significantly highly rated the quality of service they provided as compared to males. 24 Although this study assessed self-reported level of involvement of pharmacists and druggists, it seems that males were less involved in the activities that should be carried out to handle DRP and in cooperating with other health-care professionals. So we recommend further study to find out specific barriers unique to these groups.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are consistent with the result from a previous study which reported that female pharmacists were significantly more involved than males in providing general health promotion services and significantly highly rated the quality of service they provided as compared to males. 24 Although this study assessed self-reported level of involvement of pharmacists and druggists, it seems that males were less involved in the activities that should be carried out to handle DRP and in cooperating with other health-care professionals. So we recommend further study to find out specific barriers unique to these groups.…”
Section: Discussionmentioning
confidence: 94%
“…First, community pharmacists generally find the lack of time as a major barrier of proper counseling [54]. Moreover, as reported in several community pharmacists-based surveys, lack of employer reimbursement and lack of professional fees discourage community pharmacists from providing effective patient counseling services [55,56]. In Egypt, many community pharmacy employers measure their staff pharmacists’ efficiency by the volume of filled prescriptions and the number of sold medications.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in many community pharmacists-based surveys, pharmacists consider patients’ attitudes to be one of the major barriers toward effective counseling [54,56,61]. Moreover, several population-based reports in the Middle East showed that large proportions of the participants think of pharmacists as mere vendors [62,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…A similar high involvement of pharmacists in related health promotion services were reported among community pharmacists in Malaysia, reported that they are also highly contributed in education for chronic diseases such as diabetes and hypertension. 16 In Ethiopia, pharmacists are engaged in health promotion activities, although lack of training has limited their level of involvement and practice variability was noted on level of educational and pharmacy ownership 17 .…”
Section: Discussionmentioning
confidence: 99%